"Scrocco" as a Lifestyle (Also Mine) - Konarska, Justyna (ItaliAMO: Promotion of Italian Studies in the Academic and Non-Academic Environment, 2023)
The paper assumed the form of an interview with young Italian people who describe and exemplify a generally unknown cultural phenomenon named scrocco.